Perancangan dan Pembuatan Visualisasi Data Dana Penelitian Internal dan Hibah Dikti LPPM Universitas Multimedia Nusantara - Wenni Indriani Loka; Friska Natalia (ULTIMA InfoSys, 2019)
Multimedia Nusantara University is one of the private universities that has a division of the Institute for Research and Community Service or called LPPM. LPPM Division is in charge of arranging licensing conducted in the university environment, whether conducted by lecturers and students. To be able to issue licenses, especially those related to funds, LPPM should look at the existing track record so that the permits issued are not available funds and the funds to be budgeted will be sufficient for the needs of the research fund to be conducted next in the period. Therefore, the role of Business Analyst in the LPPM division is required to visualize the data used, ie research, conduct various studies undertaken by the study program within a certain period, complete funds, and other details such as research title, research category, and name or conduct research others. research. Data visualization will facilitate LPPM in monitoring existing research and become a useful tool in research licensing decisions.